2018
DOI: 10.1002/adsc.201800605
|View full text |Cite
|
Sign up to set email alerts
|

Bispentiptycenyl‐N‐Heterocyclic Carbene (NHC) Gold Complexes: Highly Active Catalysts for the Room Temperature Hydration of Alkynes

Abstract: The virtually quantitative, room temperature hydration of various terminal and internal alkynes in methanol/water requires between 0.01-0.05 mol% of [AuCl(NHC)] activated with 1.5 equiv. of silver triflate and 45 equiv. of triflic acid (both relative to gold complex) with ton of up to 300.000. Iptycenyl-substituted NHC ligands play the key role and the most efficient NHC ligand is characterized by a hemispherical shape formed by two N-pentiptycenyl substituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…The selectivity of the system is determined by different factors and can be tuned by modifying the adopted reaction condition, depending on the desired product [35]. The ketones obtained upon acetal hydrolysis are also valuable products and the alcohol route, with the on-purpose addition of one equivalent of water for promoting the hydrolysis, is among the most efficient synthetic strategy to obtain these products starting from alkynes [36,37]. Considering the rather complex mixture that is possible to obtain in the hydroalkoxylation of alkynes, the complexity of which can be even enhanced by using nonsymmetric alkynes, the catalytic performances of the complexes used herein have been initially ranked based only on the achieved alkyne conversion.…”
Section: Screening Of the Reaction Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivity of the system is determined by different factors and can be tuned by modifying the adopted reaction condition, depending on the desired product [35]. The ketones obtained upon acetal hydrolysis are also valuable products and the alcohol route, with the on-purpose addition of one equivalent of water for promoting the hydrolysis, is among the most efficient synthetic strategy to obtain these products starting from alkynes [36,37]. Considering the rather complex mixture that is possible to obtain in the hydroalkoxylation of alkynes, the complexity of which can be even enhanced by using nonsymmetric alkynes, the catalytic performances of the complexes used herein have been initially ranked based only on the achieved alkyne conversion.…”
Section: Screening Of the Reaction Conditionsmentioning
confidence: 99%
“…Catalysts 2020, 10, 1 4 of 14 obtain these products starting from alkynes [36,37]. Considering the rather complex mixture that is possible to obtain in the hydroalkoxylation of alkynes, the complexity of which can be even enhanced by using nonsymmetric alkynes, the catalytic performances of the complexes used herein have been initially ranked based only on the achieved alkyne conversion.…”
Section: Screening Of the Reaction Conditionsmentioning
confidence: 99%
“…More recent research on gold-based catalysts for this reaction has led to the individuation of Buchwald biphenylphosphine-based gold(I) complexes that exhibit comparable or even superior performance compared to Nolan's NHC-Au compounds [36][37][38][39]. Key to success was the use of electron-rich but also very bulky phosphine as ligands, which beside acting as strong electron donors are also able to protect the gold center from decomposition reactions and to avoid the formation of catalytically inactive dinuclear complexes of type C (Scheme 2).…”
Section: Effect Of the Ligandmentioning
confidence: 99%
“…In a systematic study, Xu and Hammond demonstrated that the observed catalytic performance of the complexes is much more sensitive to the steric bulk of the ligand than to the electronic properties, and individuated complexes of type 2 as the best of this kind [37]. Similarly, in 2018 the group of Plenio developed the synthesis of extremely bulky bispentiptycenyl-NHC ligands and of their gold(I) complexes (e.g., complex 3) [39].…”
Section: Effect Of the Ligandmentioning
confidence: 99%
“…Internal alkynes were much less reactive and even at 12 mol % catalyst loading the reaction of 3-hexyne and PhCONHNH 2 yielded the respective addition product in only 32% yield, with diphenylacetylene only 12% of the addition product were obtained. We recently reported the excellent activity of the very bulky bispentiptycenyl-substituted (NHC)Au complexes in the hydration of terminal and internal alkynes [43] as well as in other transition-metal-catalyzed transformations [44,45]. We were now interested, whether catalysts with such ligands also display high activities in other gold-catalyzed reactions.…”
Section: Introductionmentioning
confidence: 99%